2018
DOI: 10.1021/acsami.8b19249
|View full text |Cite
|
Sign up to set email alerts
|

Microporous and Flexible Framework Acoustic Metamaterials for Sound Attenuation and Contrast Agent Applications

Abstract: The low-frequency (100−1250 Hz) acoustic properties of metal− organic framework (MOF) materials were examined in impedance tube experiments. The anomalously high sound transmission loss of FeBTC, quantitatively demonstrated that these prototypical MOFs are absorptive acoustic metamaterials. To the best of our knowledge, this is the first example of MOFs that have been demonstrated to be acoustic metamaterials. Low-frequency acoustic dampening by subwavelength MOF metamaterials is likely due to sound dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…6 Notably, the molecular-scale architecture of these "meta-MOFs" routinely produces responses difficult to engineer on the macroscale, such as negative thermal expansion (NTE) [9][10][11] and other optical phenomena. 12,13 While most of these properties are based on elastic deformations of the crystal lattice, several MOFs are known to undergo large scale inelastic transitions under preservation of the framework connectivity. These so-called soft porous crystals (SPCs) 14 or flexible MOFs 15 exhibit strong deformation of the lattice in particular upon adsorption or desorption of guest species.…”
Section: Introductionmentioning
confidence: 99%
“…6 Notably, the molecular-scale architecture of these "meta-MOFs" routinely produces responses difficult to engineer on the macroscale, such as negative thermal expansion (NTE) [9][10][11] and other optical phenomena. 12,13 While most of these properties are based on elastic deformations of the crystal lattice, several MOFs are known to undergo large scale inelastic transitions under preservation of the framework connectivity. These so-called soft porous crystals (SPCs) 14 or flexible MOFs 15 exhibit strong deformation of the lattice in particular upon adsorption or desorption of guest species.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that polymers may reduce access to MOF pore networks, and the polymers themselves may even partially occupy the pore volume. However, this polymer-coated MOF arrangement should not negatively impact their utility as acoustic contrast agents, as solvent-bearing (unactivated) MOFs still interact with acoustic waves, 9 and the polymers may even increase lowfrequency attenuation, similar to the behavior of long-chain hydrocarbons. 24 As expected, the addition of polymer coatings altered the hydrodynamic and electrokinetic properties of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 We recently demonstrated that MOFs are low-frequency absorptive acoustic metamaterials, exhibiting anomalous sound transmission loss and tunable resonances from 100-1250 Hz. 9 These emergent lowfrequency properties make MOFs desirable for sound-attenuating applications, including for use as geophysical contrast agent. We have also demonstrated that rocks saturated with MIL-101(Cr) 10 nano uids (~0.5 wt%) have distinct elastic and anelastic properties, resulting in decreased seismic wave velocities and amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, porous MOFs have shown promising application potential in gas storage and separation, catalysis, and drug delivery [2]; on the other hand, this emergent class of materials can exhibit diverse physical properties, including fluorescence, ferromagnetism, ferroelectricity, and multiferroicity [3][4][5][6][7]. Although there are numerous studies on the diverse properties and functionalities of MOFs [8], little attention has been paid to exploring an important area, namely, the acoustic properties [9]. Very recently, the application of acoustics and energy-transfer mechanisms in MOFs has been experimentally validated [10,11], which prompts the necessity to systematically study the acoustic properties of MOFs.…”
Section: Introductionmentioning
confidence: 99%